Isolation and FTIR-ATR and 1H NMR Characterization of Alginates from the Main Alginophyte Species of the Atlantic Coast of Morocco - Belattmania, Z (2020)
Alginates are widely used as gelling agents in textile print pastes, medical industries, impression material in dentistry, and anticoagulant material in toothpaste. In the present study, the content and spectroscopic characterization (1H NMR and FT-IR) of the sodium alginates were investigated in the eight brown seaweeds Sargassum muticum, Fucus vesiculosus f. volubilis, Carpodesmia tamariscifolia, Bifurcaria bifurcata, Laminaria ochroleuca, Cystoseira humilis, Saccorhiza polyschides, and Fucus guiryi harvested from the NW Atlantic coast of Morocco. The results proved that the most studied algae depicted alginate yields higher than 18% dry weight. The FT-IR analysis showed that the spectra of the extracted alginates exhibited significant similarities to the commercial alginate from Sigma-Aldrich. The 1H NMR spectroscopy indicated that the extracted alginates have a high content of β-d-mannuronic (M) than α-l-guluronic acid (G) with M/G ratio values ranging from 1.04 to 4.41. The homopolymeric fractions FMM are remarkably high compared to the FGG and heteropolymeric fractions (FGM = FMG) especially for F. guiryi, C humilis, C. tamariscifolia, L. ochroleuca, and S. polyschides. Nevertheless, the heteropolymeric fractions (FGM/FMG) are quite abundant in the alginates of S. muticum, F. vesiculosus f. volubilis, and B. bifurcata accounting for more than 52% of the polymer diads. Based on these results, the investigated algal species (except Fucus guiryi and Bifurcaria bifurcata) could be regarded as potential sources of alginates for industrial uses.